MRI management of focal liver lesions: what a beginner cannot fail to know - Granata, Vincenza; Fusco, Roberta; Simonetti, Igino; Riga, Maria Giovanna; Pellegrino, Giuseppe; Carriero, Serena; Karaboue, Michele Ahmed Antonio; Carrafiello, Gianpaolo; Petrillo, Antonella; Izzo, Francesco (Frontiers in Oncology, 2025)
Magnetic resonance imaging (MRI) is currently recognized as the most suitable diagnostic tool for the detection and characterization of focal liver lesions. The combination of morphological and functional data allows, in different clinical scenarios, high diagnostic performance in characterizing even very small lesions, thereby improving patient management while reducing costs and examination time. Despite this premise, MRI should not be prescribed for all patients with focal liver lesions. Indications must be clearly understood, and the individual characteristics of each patient must be considered. For different clinical scenarios, depending on the presence of extrahepatic malignancy or known liver disease, MRI with contrast agents represents a useful diagnostic tool, although the choice will also depend on operator experience, technology availability, and patient-specific characteristics. A standard protocol should include conventional sequences: T2-weighted (T2W) sequences, T2W sequences with fat suppression (FS), and in-phase and opposed-phase gradient-echo T1 sequences, along with functional sequences. Among functional techniques, diffusion-weighted imaging (DWI) is mandatory, particularly for detecting very small lesions; however, diffusion restriction does not necessarily indicate malignancy. Contrast-enhanced MRI remains the cornerstone of liver MRI, especially for lesion categorization. Contrast agents can be classified as non-specific agents, which distribute into vascular and extracellular extravascular spaces, and specific agents, which are taken up by hepatic cells (Kupffer cells or hepatocytes). The abbreviated protocol concept is based on the premise that, within a shorter examination time, it is possible to acquire the essential information needed for patient management using only selected sequences from a standard protocol. Radiomics has emerged as a promising tool in liver oncology, particularly for evaluating colorectal liver metastases. To fully realize the clinical value of radiomics, it is essential to overcome several methodological hurdles, including the standardization of image acquisition and analysis workflows and rigorous validation across large and diverse patient cohorts. The aim of this review, designed for beginners in liver MRI, is to provide a comprehensive overview of the management of focal liver lesions, with a focus on acquisition protocols (including abbreviated protocols), contrast media, and reporting strategies to ensure accurate lesion characterization.